(untitled) (Research, Society and Development, 2020)
Sepsis is a systemic inflammatory response caused by an infection, which can progress to severe sepsis, septic shock and death. The objective was to identify the scientific evidence regarding the role of nurses in the prevention and identification of signs and symptoms of sepsis in intensive care. This is an integrative review of a qualitative approach carried out in September, in the MEDLINE, BDENF, LILACS and IBECS databases, through the Virtual Health Library (VHL), articles in English, Spanish and Portuguese were included in the period from 2010 to 2020, selecting 10 articles through exploratory and critical reading of the titles, abstracts and results achieved in the studies. Of the selected articles, 70% (N = 7) were found on MEDLINE, 10% (N = 1) on LILACS, 20% (N = 2) BDENF / LILACS. It was observed that the number of published works was greater in the years 2010, 2011, 2017 and 2019 with two articles in the respective years, followed by the years 2015 and 2020, with one study each year. Among the articles, 90% (N = 9) were published in English and 10% (N = 1) in Portuguese. According to the syntheses of the studies analyzed, it is observed that the participation of nursing starts at the moment of awareness with health teams, in the creation of methods to identify sepsis, in addition to the identification of the importance of the screening packages and tools conducted nursing. In addition, it is necessary that nurses seek to have basic notions of systemic changes caused by sepsis, whether they are related to hemodynamic, neurological, respiratory, renal and nutritional changes.